The Influence of Instagram Digital Marketing and Brand Image on Purchase Decisions - Gunaprya, Komang Rosemalla Dewi; Putra P, Komang Widhya Sedana (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
Since the dawn of the digital era, social media, especially Instagram, has become a key platform influencing customer behavior and purchasing decisions. Previous studies have focused mainly on well-established beauty brands and few are aware of how digital marketing and brand image affect consumer preference towards domestically manufactured beauty products. This study aims to investigate how digital marketing influences Instagram and brand image towards the buying decision of consumers of Namimi beauty products in Denpasar City. Utilizing a quantitative research approach, data were collected via questionnaires from 60 respondents between 18 and 35 years old who had purchased Namimi products at least once. Validity, reliability, classical assumption tests, multiple linear regression, t-test, F-test, and coefficient of determination analysis were employed in the analysis. The results showed that both brand image and Instagram digital marketing both partially and jointly have a significant and positive impact on purchase decision. The adjusted R² of 0.511 indicates that 51.1% of consumer purchase decision is explained by these two variables while the remaining 48.9% is explained by other variables. These results are used to highlight the importance of having a strong brand image and strong online promotion using Instagram to strengthen consumer purchasing behavior. Future research is proposed to use more variables such as product quality, influencer credibility, and customer engagement to provide a complete picture of how consumers make purchasing decisions in the local beauty market.